2022
DOI: 10.3389/fgene.2022.996950
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of m7G modification patterns based on potential m7G regulators and tumor microenvironment infiltration characterization in lung adenocarcinoma

Abstract: Background: The non-negligible role of epigenetic modifications in cancer development and tumor microenvironment (TME) has been demonstrated in recent studies. Nonetheless, the potential regulatory role of N7-methylguanosine (m7G) modification in shaping and impacting the TME remains unclear.Methods: A comprehensive analysis was performed to explore the m7G modification patterns based on 24 potential m7G regulators in 817 lung adenocarcinoma (LUAD) patients, and the TME landscape in distinct m7G modification p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In adrenocortical carcinoma, immunofluorescence revealed that high expression of METTL1 in tumor cells was inversely proportional to CD8 + T and directly proportional to the infiltration rate of macrophages [ 98 ]. Numerous bioinformatic analyses have also demonstrated that m7G modification related regulators, as well as lncRNAs, have important impact on TME [ 98 , 104 , 105 ].…”
Section: Roles Of M7g Modification In the Tumor Immune Microenvironmentmentioning
confidence: 99%
“…In adrenocortical carcinoma, immunofluorescence revealed that high expression of METTL1 in tumor cells was inversely proportional to CD8 + T and directly proportional to the infiltration rate of macrophages [ 98 ]. Numerous bioinformatic analyses have also demonstrated that m7G modification related regulators, as well as lncRNAs, have important impact on TME [ 98 , 104 , 105 ].…”
Section: Roles Of M7g Modification In the Tumor Immune Microenvironmentmentioning
confidence: 99%